A study on â€œAn Employee Diversity and Inclusion in a Higher Educational Institutionsâ€ - C, Kavitha; ., . (International Journal of Engineering and Technology, 2018)
One of the greatest challenges facing faculties and management today is the rapid pace at which the work force is changing across the globe. Generational turnover, Cultural Revolution, widespread immigration, typical competition, and advancing technology have all played and will continue to play a major role in creating a comfortable environment is increasingly complex,Â institution and its ecosystem that both breaks down old and creates new barriers to recruiting, developing and retaining talented facultiesÂ are the great barriers to recruiting, developing and retaining talent work place diversity has gained currency in 3 Câ€™s suits around the world as best faculties seek to develop a more cohesive collaborative and creative work environment as a means of driving continued growth. Diversity has many facets including race, ethnicity, gender, age, religious and sexual orientation etc. Diversity is the range of human difference including but not limited to race, ethnicity, gender identity, sexual orientation age, social class, physical ability or attributes religion ethical value system, national origin and political belief. Inclusion is involvement and empowerment. Where the inherent worth and dignity of all people are recognized. In a nutshell itâ€™s about empowering people by respecting and appreciating what makes them difference in terms of age, gender, ethnicity, religion, disability, sexual, orientation education and national origin. The objectives of the study are to know the significance of diversity and inclusion to educational institutions. To analyze the need of diversity and inclusion in an organizations. This article is written on the basis of secondary data; mainly analysis is done on the basis of the different case studies relating to diversity and inclusions. The main limitation of the study is this paper is written on the basis of secondary sources which are collected from the internet, journals, and articles and textbooks etc. this study is done by considering higher educational institutions. Lastly conclusions can be drawn that diversity and inclusions are very important of any organizations, because of these the organization can be run successfully and organization can leading successfully in a society.Â Â